Molecular docking of gallic acid as anti-photoaging in silico - Dewi, Ni Kadek Diah Parwati; Suryadewi, Kadek Dinda; Fitriari, Diah Mawarni; Andini, Kadek Lia; Laksmiani, Ni Putu Linda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
Skin aging caused by excessive exposure to ultraviolet is known as photoaging. The mechanism underlying skin photoaging relates to collagen degradation in the extracellular matrix (ECM) by overexpression of matrix metalloproteinases-1 (MMP-1). Gallic acid is a phenolic antioxidant found in many types of plants and can be used as an anti-photoaging agent due to its antioxidant activity. This study aims to determine the potential effect of gallic acid as an anti-photoaging against MMP-1 using in silico molecular docking. The stages included gallic acid structure optimization using the HyperChem 8, preparation of protein target MMP-1 (PDB ID: 966C) using the Chimera1.10.1, validation the molecular docking protocol, and docking gallic acid on MMP-1 with the Autodock 1.5.6. The results showed that gallic acid had an affinity for MMP-1 with a binding energy of -6.0 kcal/mol. There are similar amino acid residues in hydrogen bonds between the native ligand RS2 with MMP-1 and gallic acid with MMP-1, namely ALA 182, LEU 181, and HIS 218. The results suggest that gallic acid has the potential as the anti-photoaging agent through the inhibition of the MMP-1 enzyme.